Electrochemical and physical properties of magnesioferrite nanomaterial and photocatalytic degradation of methylene blue - Nolubabalo Matinise; A. Fall (Scientific Reports)
Abstract This research successfully synthesized semiconductive magnesioferrite (MgFe2O4) nanomaterials using a green chemistry method that utilizes the natural extract of Moringa olefeira serving as both a reducing and oxidizing agent. The optical characteristics and crystalline structure of the MgFe2O4 nanomaterials were analysed using photoluminescence, diffuse reflectance spectroscopy, and X-ray diffraction. Additionally, Fourier transform infrared spectroscopy provided valuable insights into the chemical bonding and composition. High-resolution transmission electron microscopy was employed to obtain extensive information on crystalline size and distribution. Furthermore, the electrochemical properties were assessed through cyclic voltammetry and electrochemical impedance spectroscopy, revealing an excellent voltametric response and pseudo-capacitive behaviour associated with faradaic reactions, as well as outstanding conductivity linked to the unique charge transport mechanisms present in the MgFe2O4 structure. The effectiveness of the MgFe2O4 nanomaterials in the photodegradation of methylene blue from aqueous solutions was evaluated under visible light irradiation. Photocatalytic experiments measured the influence of various parameters, including catalyst loading, dye concentration, and pH. The MgFe2O4 nanomaterials exhibited impressive photocatalytic degradation efficiency, achieving an 81% degradation rate at pH 5.0 within 120 min. Kinetic studies indicated that the degradation process adhered to a pseudo-first-order model, with a rate constant of 0.01533 min−1, signifying a rapid reaction under optimal conditions. This study provides a thorough understanding of the electrochemical properties and enhanced photocatalytic capabilities of MgFe2O4 nanomaterials, thereby advancing green nanotechnology for environmental remediation.